Tata Kelola Kolaborasi dalam Penanganan Kemiskinan di Kota Yogyakarta: Studi Kasus Program “Gandeng-Gendong” - Eka Putra; Nova Elsyra; Muchamad Zaenuri (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2020)
Collaborative Governance conducted by five stakeholders (City Government, Corporations, Campuses, Communities, and Villages) in an effort to reduce poverty in Yogyakarta City. This study uses a collaborative governance theory approach which is seen from the aspects of empowering micro and small economies, improving welfare and empowering the environment through CSR (corporate social responsibility). In researching the Yogyakarta City Handling and Collaboration program researchers used qualitative methods. The results showed that the collaborative governance carried out had a positive impact on the economy of the people of Yogyakarta City. The Handling and Carrying Program has provided employment certainty, the community is equipped (soft skills and hard skills) and the community's economy is improving well. But in addition to the many benefits from the presence of the Gandeng Gendong program there are also weaknesses of the stakeholders, namely the lack of program socialization, training and empowerment, so that the effect of the worsening of the program implementation can not be said to be the maximum presence of the Gandeng Gendong program to the economy of the people of Yogyakarta City.